Different Effect of Sox11 in Retinal Ganglion Cells Survival and Axon Regeneration - Li, Ying; Struebing, Felix L.; Wang, Jiaxing; King, Rebecca; Geisert, Eldon E. (Frontiers in Genetics, 2018)
Purpose: The present study examines the role of Sox11 in the initial response of retinal ganglion cells (RGCs) to axon damage and in optic nerve regeneration in mouse. Methods: Markers of retinal injury were identified using the normal retina database and optic nerve crush (ONC) database on GeneNetwork (www.genenetwork.org). One gene, Sox11, was highly upregulated following optic nerve crush. We examined the role of this transcription factor, Sox11, following ONC and optic nerve regeneration in mice. In situ hybridization was performed using the Affymetrix 2-plex Quantigene View RNA In Situ Hybridization Tissue Assay System. Sox11 was partially knocked out by intravitreal injection of AAV2-CMV-Cre-GFP in Sox11f/f mice. Optic nerve regeneration model used Pten knockdown. Mice were perfused and the retinas and optic nerves were dissected and examined for RGC survival and axon growth. Results: Sox11 was dramatically upregulated in the retina following ONC injury. The level of Sox11 message increased by approximately 8-fold 2 days after ONC. In situ hybridization demonstrated low-level Sox11 message in RGCs and cells in the inner nuclear layer in the normal retina as well as a profound increase in Sox11 message within the ganglion cells following ONC. In Sox11f/f retinas, partially knocking out Sox11 significantly increased RGC survival after ONC as compared to the AAV2-CMV-GFP control group; however, it had little effect on the ability of axon regeneration. Combinatorial downregulation of both Sox11 and Pten resulted in a significant increase in RGC survival as compared to Pten knockdown only. When Pten was knocked down there was a remarkable increase in the number and the length of regenerating axons. Partially knocking out Sox11 in combination with Pten deletion resulted in a fewer regenerating axons. Conclusion: Taken together, these data demonstrate that Sox11 is involved in the initial response of the retina to injury, playing a role in the early attempts of axon regeneration and neuronal survival. Downregulation of Sox11 aids in RGC survival following injury of optic nerve axons, while a partial knockout of Sox11 negates the axon regeneration stimulated by Pten knockdown.